STUDENT PERSPECTIVES OF UDAYANA UNIVERSITY MEDICALSTUDENTS ON THE USE OF CHAT-GPT IN THE LEARNING PROCESS FOR THE CLASS OF 2021 - Husodo, Abraham Christopher; Manuaba, Ida Bagus Amertha Putra Putra; Darmayani, I Gusti Ayu Sri; Sundariyati, I Gusti Ayu Harry (E-Jurnal Medika Udayana; Vol 14 No 03 (2025): E-Jurnal Medika UdayanaDO - 10.24843/MU.2025.V14.i3.P16, 2025)
Artificial intelligence (AI) is a testament to technological advancement aimed at assisting human survival. One form of AI that is frequently used today is ChatGPT. ChatGPT is widely utilized among students, including medical students, due to its numerous benefits. However, there has yet to be a comprehensive understanding of how ChatGPT is viewed in student’s learning process. This study aims to determine the perspectives of Udayana University medical students from the class of 2021 regarding the use of ChatGPT in the learning process. This research is a quantitative descriptive study employing a cross-sectional approach. Data collection was conducted using a Google Form questionnaire with 71 medical undergraduate students. Data analysis was performed using SPSS version 26.0. From the 14 statements in the questionnaire, the majority of respondents agreed that the use of ChatGPT aids their learning process, such as easily accessing information, personalizing the learning process, and so on. The drawbacks of ChatGPT perceived by respondents include its inability to search for scientific journal sources for research purposes. For Udayana University medical students, using ChatGPT in the learning process offers more advantages than disadvantages. The presence of ChatGPT assists these students in their studies. Keywords: ChatGPT, medical students, students, study process